1979
DOI: 10.1093/ajcn/32.3.607
|View full text |Cite
|
Sign up to set email alerts
|

Physical growth: National Center for Health Statistics percentiles

Abstract: Anthropometry is an effective and frequently performed child health and nutrition screening procedure. The value of physical growth data depends on their accuracy and reliability, how they are recorded and interpreted, and what follow-up efforts are made after identification of growth abnormality. The new National Center for Health Statistics percentiles can be used to improve identification of potential health and nutritional problems and to facilitate the epidemological comparison of one group of children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
915
1
97

Year Published

1987
1987
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,187 publications
(1,031 citation statements)
references
References 7 publications
18
915
1
97
Order By: Relevance
“…Since an important symptom of established HIV-infection (AIDS) is severe weight loss, we excluded children who were wasted (weight-for-height below or equal to 72 s.d. of the median of the National Center of Health Statistics (NCHS) reference population) (Hamill et al, 1979). All communication with the mothers of the children was carried out by the local staff of the study team, who werē uent in the local language, Cibemba.…”
Section: Design and Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since an important symptom of established HIV-infection (AIDS) is severe weight loss, we excluded children who were wasted (weight-for-height below or equal to 72 s.d. of the median of the National Center of Health Statistics (NCHS) reference population) (Hamill et al, 1979). All communication with the mothers of the children was carried out by the local staff of the study team, who werē uent in the local language, Cibemba.…”
Section: Design and Subjectsmentioning
confidence: 99%
“…For all children height-for-age-(HAZ), weight-for-age-(WAZ), and weight-for-height-Z-scores (WHZ) were calculated using the NCHS reference (Hamill et al, 1979). Children were classi®ed into two groups according to their height-for-age Z-score: stunted (HAZ472) and nonstunted (HAZ b 72) (WHO Working Group, 1986).…”
Section: Anthropometrymentioning
confidence: 99%
“…The subjects had appropriate weight-for-height but their height-for-age ranged from 0.5 to À2.5 s.d. of the NCHS references (Hamill et al, 1979), indicating some degree of stunting. Mothers reported that the children were born at term except one for which there was no record in the hospital docket.…”
Section: Resultsmentioning
confidence: 99%
“…There was always a significant positive relationship between nitrogen intake and the three urea kinetic variables (production, excretion and hydrolysis) in the base model and all the other models. When energy intake was added to the base model, there was a significant negative association Expressed as the median for a child of the same age or the same height (Hamill et al, 1979). between energy intake and the urea kinetic variables and this model accounted for most of the variance of urea production (Table 3) and urea hydrolysis (Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation